Gut Microbiota and Cardiovascular Disease: Symbiosis Versus Dysbiosis - Manolis, Antonis A.; Manolis, Theodora A.; Melita, Helen; Manolis, Antonis S. (Current Medicinal Chemistry, 2022)
The gut microbiome interacts with host physiology through various mechanisms, including the cardiovascular (CV) system. A healthy microbiome has the ability to process and digest complex carbohydrates into short-chain fatty acids (SCFA). These SCFA function as signaling molecules, immune-modulating molecules, and energy sources. However, when the microbiome is altered, it produces gut dysbiosis with overgrowth of certain bacteria that may lead to overproduction of trimethylamine-N-oxide (TMAO) from the metabolism of phosphatidylcholine, choline, and carnitine; dysbiosis also leads to increased intestinal permeability allowing the microbiome-derived lipopolysaccharide (LPS), a bacterial endotoxin, to enter the blood circulation, triggering inflammatory responses. An altered gastrointestinal (GI) tract environment and microbiome- derived metabolites are associated with CV events. Disrupted content and function of the microbiome leading to elevated TMAO and LPS levels, altered bile acid metabolism pathways, and SCFA production are associated with an increased risk of CV diseases (CVD), including atherosclerosis, myocardial infarction, thrombosis, arrhythmias, and stroke. Therapeutic interventions that may favorably influence a dysbiotic GI tract profile and promote a healthy microbiome may benefit the CV system and lead to a reduction of CVD incidence in certain situations. These issues are herein reviewed with a focus on the spectrum of microbiota-related CVD, the mechanisms involved, and the potential use of microbiome modification as a possible therapeutic intervention.
Keywords: Microbiome